2001
DOI: 10.1007/s002030100271
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a periplasmic nitrate reductase in Azospirillum brasilense Sp245

Abstract: The Azospirillum brasilense Sp245 napABC genes, encoding nitrate reductase activity, were isolated and sequenced. The derived protein sequences are very similar throughout the whole Nap segment to the NapABC protein sequences of Escherichia coli, Pseudomonas sp. G-179, Ralstonia eutropha, Rhodobacter sphaeroides, and Paracoccus denitrificans. Based on whole-cell nitrate reductase assays with the artificial electron donors benzyl viologen and methyl viologen, and assays with periplasmic cell-free extracts, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…denitrificans (Liu et al, 1999), Pseudomonas sp. G-179 (Bedzyk et al, 1999), Pseudomonas aeruginosa PAO1 (Stover et al, 2000), Azospirillum brasilense (Steenhoudt et al, 2001) and Sinorhizobium meliloti (Galibert et al, 2001). In the N-terminal region of NapA, the sequence 7 DRRQMLK 14 corresponds closely to the twin arginine motif identified in a large number of periplasmic metalloproteins that are exported via the Sec-independent TAT translocon .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…denitrificans (Liu et al, 1999), Pseudomonas sp. G-179 (Bedzyk et al, 1999), Pseudomonas aeruginosa PAO1 (Stover et al, 2000), Azospirillum brasilense (Steenhoudt et al, 2001) and Sinorhizobium meliloti (Galibert et al, 2001). In the N-terminal region of NapA, the sequence 7 DRRQMLK 14 corresponds closely to the twin arginine motif identified in a large number of periplasmic metalloproteins that are exported via the Sec-independent TAT translocon .…”
Section: Resultsmentioning
confidence: 99%
“…G-179 (Bedzyk et al, 1999), Rhodobacter sphaeroides f. sp. denitrificans (Liu et al, 1999), and Azospirillum brasilense Sp245 (Steenhoudt et al, 2001).…”
Section: Nitrate (Nomentioning
confidence: 99%
“…It is known that nitrate and nitrite reduction performed by A. brasilense Sp245 affects the plant-bacterial interactions and the growth of the host plants [12,22]. As shown in this study, several spontaneous super-swarming derivatives of A. brasilense Sp245 have different DNA patterns and behave differently in the presence of NO 3 -/NO 2 -.…”
Section: Growth and Motility Of The A Brasilense Wild-type And Supermentioning
confidence: 61%
“…Nitrite produced by azospirilla in liquid MPSS with KNO 3 could be the product of assimilatory or dissimilatory nitrate reduction. Although, as an alternative form of respiration, denitrification mainly occurs when O 2 concentrations are limiting, various bacterial species, including A. brasilense, are also capable of aerobic dissimilatory reduction of N oxides [12,22].…”
Section: Growth and Motility Of The A Brasilense Wild-type And Supermentioning
confidence: 99%
“…In contrast the periplasmic nitrate reductase can be referred to as a dissimilatory enzyme because it can be expressed under both aerobic and anaerobic conditions but it cannot generate proton motive force during electron transfer in the quinol-Nap span (Steenhoudt et al 2001;Gates et al 2003). Western blot analysis was performed and showed that the intensity of the ~140 kDa band of NarG, a catalytic subunit of membranebound nitrate reductase, was similar under conditions containing only Fe 3+ or Fe 3+ and Mo 6+ (data not shown).…”
Section: Discussionmentioning
confidence: 99%